6x+32=11x-3

Simple and best practice solution for 6x+32=11x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+32=11x-3 equation:


Simplifying
6x + 32 = 11x + -3

Reorder the terms:
32 + 6x = 11x + -3

Reorder the terms:
32 + 6x = -3 + 11x

Solving
32 + 6x = -3 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
32 + 6x + -11x = -3 + 11x + -11x

Combine like terms: 6x + -11x = -5x
32 + -5x = -3 + 11x + -11x

Combine like terms: 11x + -11x = 0
32 + -5x = -3 + 0
32 + -5x = -3

Add '-32' to each side of the equation.
32 + -32 + -5x = -3 + -32

Combine like terms: 32 + -32 = 0
0 + -5x = -3 + -32
-5x = -3 + -32

Combine like terms: -3 + -32 = -35
-5x = -35

Divide each side by '-5'.
x = 7

Simplifying
x = 7

See similar equations:

| -4x+8y=56 | | X-2+x-2+x-2=294 | | 3x-8=8-33 | | -6y+5=-12 | | x-2=4-2 | | 4(n+2)(n+5)=0 | | 3q^2=-5 | | 0.4+2=24 | | 4x=log(3)8x-2 | | 10y=-20 | | -6-x=0 | | 3x=(78,6*5)2 | | x=(78,6*5)2 | | y-4=5 | | k^2-3k=10 | | 3z-2z-6= | | 15-4(x-3)=x-3 | | 13+9x=-21x-17 | | 3z-2z+6= | | 7x-4=3x+2(x+3) | | -5-5y=-20 | | 0-5y=-20 | | z+2=10 | | 5m+10n= | | 9=6-2x | | 12+4y=8 | | -3(x-1)+2x=10 | | 2x^2+3x=6 | | -6y-6=10+5y | | 4.5x^2-3.7x-7.4=0 | | 1.2*1.5=1.8 | | 9x-21=35+x |

Equations solver categories